The scope of the parties' will in resolving commercial disputes through expedited arbitration. - Saleh, Mustafa Natiq; Tawfiq, Rabab Raad (Journal of Legal and Political Studies, 2025)
The commercial arbitration system represents one of the most important means of resolving commercial disputes, and the will of the disputing parties is fundamentally prominent in it, as this will regulates many matters in the field of traditional commercial arbitration. With the presence of various and new developments in this system, we find the emergence of the expedited (rapid) commercial arbitration system, as the will of the parties enjoys a lot of freedom and a wide scope in this new type of arbitration compared to traditional arbitration, in which the will may be absent at times. However, the subject requires identifying the expedited (rapid) commercial arbitration system and distinguishing it from traditional and emergency arbitration and explaining the importance of the existence of expedited arbitration and then focusing and searching through the comparative legal rules regulating the subject on the extent of the intervention and organization of the will of the parties to the procedures for resolving the dispute through expedited arbitration and its scope and impact on it. Keywords: Expedited arbitration, dispute, parties, arbitrator, arbitration centers
Keywords: Expedited arbitration; dispute; parties; arbitrator; arbitration centers